Explicit formulation of a nodal transport method for discrete ordinates calculations in two-dimensional fixed-source problems - A. Tres, C. B. Picoloto, R. D. Da Cunha; Barichello, L.B. (Kerntechnik (1987), 2014)
n/a
n/a